The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s10404-007-0221-0
|View full text |Cite
|
Sign up to set email alerts
|

Nanohole arrays in metal films as optofluidic elements: progress and potential

Abstract: Subwavelength holes in metal films exhibit coupled optical phenomena specific to structure geometry, incident light and properties of the near-surface medium. As optofluidic components, nanohole arrays in metal films present several opportunities. This review provides an overview of the unique optical characteristics of such arrays, with emphasis on their application in the micro and nano-fluidic environment. The majority of contributions in this area have focused on sensor applications, and the results of nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 65 publications
2
62
0
2
Order By: Relevance
“…Arrays for Integrated Bio-Chemical Sensing of analyte) with nanohole arrays (as sensor elements) [2]. However, for real world applications a more complex sensor system utilizing a multitude of different nanohole arrays as a series of sensor elements, like a electronic nose is more desirable [3]- [5].…”
Section: Large-area Low-cost Flexible Plastic Nanoholementioning
confidence: 99%
“…Arrays for Integrated Bio-Chemical Sensing of analyte) with nanohole arrays (as sensor elements) [2]. However, for real world applications a more complex sensor system utilizing a multitude of different nanohole arrays as a series of sensor elements, like a electronic nose is more desirable [3]- [5].…”
Section: Large-area Low-cost Flexible Plastic Nanoholementioning
confidence: 99%
“…Integration efforts to date have largely been in concert with sensor developments and it is difficult to separate them entirely. A recent review discusses nanohole arrays as combined optofluidic (optical and fluidic) elements [224]. In this Section, an overview of the most notable integration advances to date is provided, as well as some areas for future efforts.…”
Section: Integration and Devicesmentioning
confidence: 99%
“…Among artificial nanostructures, nanohole arrays exhibit many interesting features in terms of nonlinear optics 1,[9][10][11][12][13] . Airola et al showed an enhancement of the transmitted second harmonic generation (SHG) signal in a periodic circular nanohole arrays due to the increased transmission of the incident light.…”
Section: Introductionmentioning
confidence: 99%